2000
DOI: 10.1016/s0169-4332(00)00401-3
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructions of GaN and InGaN surfaces

Abstract: The reconstruction and growth kinetics of gallium nitride (0001) and (000 ) surfaces are studied using scanning tunneling microscopy, reflection high-energy electron diffraction, and low-energy electron diffraction. Results for bare GaN surfaces are summarized, with particular attention paid to the "pseudo-1×1" reconstruction of the (0001) face. Changes in the surface structure and kinetic processes due to indium co-deposition during growth are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 22 publications
4
13
0
Order By: Relevance
“…These petal-like structures resemble those in the STM image in Ref. (Feenstra et al, 2000), where a 12×12-reconstructed structure, which had not been previously observed on (0001) or (0001) surfaces. Feenstra et al (Feenstra et al, 2000) associated this novel structure with the "1×1" Ga adlayers on GaN(0001) layers, implying the existence of an inversion domain immediately below the novel reconstruction area of the surface.…”
Section: As-received Hvpe-gan(0001) Surface Structuressupporting
confidence: 80%
See 2 more Smart Citations
“…These petal-like structures resemble those in the STM image in Ref. (Feenstra et al, 2000), where a 12×12-reconstructed structure, which had not been previously observed on (0001) or (0001) surfaces. Feenstra et al (Feenstra et al, 2000) associated this novel structure with the "1×1" Ga adlayers on GaN(0001) layers, implying the existence of an inversion domain immediately below the novel reconstruction area of the surface.…”
Section: As-received Hvpe-gan(0001) Surface Structuressupporting
confidence: 80%
“…The HVPE2 sample was grown by multistep lateral epitaxial overgrowth, and there are defects distributed inside this crystal. Thus, we associate the petal-like structure on the surface with an area with high defect density immediately below the inside of the crystal, and conclude that the petal-like structure in this study is correlated with the novel reconstruction in the prior work (Feenstra et al, 2000). The petal-like structures observed on HVPE2 samples were not observed on HVPE1 samples.…”
Section: As-received Hvpe-gan(0001) Surface Structuressupporting
confidence: 65%
See 1 more Smart Citation
“…The film's polarity is found to greatly influence surface structure and growth processes. 1,2 Different reconstructions have been identified on the surfaces of different polarities. The observation of surface reconstructions can thus be used to determine the polarity of film.…”
Section: Introductionmentioning
confidence: 99%
“…An N 2 plasma flux of ~ (1 3) 10 5 torr is supplied during the nitridation process while the sapphire is kept at 500 to 750 o C. The plasma power is at a range of 200 to 500 W. Figure 1(a) shows the RHEED pattern after the nitridation of the sapphire with the electron beam along [2 1 1 0] direction, and Figure 1(b) along [1010] direction. [9][10][11][12] They are streaky with clear Kikuchi patterns. A 200 Å buffer layer of GaN is deposited at 550 o C before the substrate temperature is raised to 700 o C to grow the epilayer.…”
Section: Resultsmentioning
confidence: 99%